(untitled) (Revista Inclusiones, 2020)
The article considers the possibilities of applying social control in order to ensure the legality and legitimacy of the formation of state power. The analysis of foreign experience in the application of control public powers in foreign countries is given; the role of election commissions and the possibilities of socialcontrol in Russia are considered. The problems of the work of election commissions and other bodies, whose powers are related to the electoral process, building the confidence of the electorate and increasing active voters in various countries, including the USA, Great Britain, Germany, France, China, are identified. Various measures aimed at improving the transparency of the electoral process and confidence in the electoral institution undertaken in foreign countries are evaluated. It was revealed that in the Russian Federation, despite the use of the institution of observers, certain legal institutions remain unclaimed. Based on an analysis of the practice and possibilities of using various forms of socialcontrol in the electoral process, proposals are made that contribute to increasing the confidence of citizens in the election institution.